2009
DOI: 10.1108/00346650910957519
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of biochemical contents of pigeon pea (Cajanus cajan(L.) Millsp)

Abstract: PurposeThe purpose of this paper is to characterize 25 collections of pigeon pea from south‐west Nigeria using nutritional and anti‐nutritional contents of the seeds.Design/methodology/approachThe nutritional and anti‐nutritional constituents of 25 collections of pigeon pea were determined. Data collected were subjected to correlation, principal components and fastclus analyses.FindingsAriation among the collections for the nutrient contents was low. Trypsin inhibitor content had the highest variability rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Most protease inhibitors or anti trypsin are proteins with domains that enter or block a protease active site to prevent substrate access. According to protein content, there is no difference among treatments but Akande and Balogun (2009) reported that protein and trypsin inhibitor contents were negatively correlated.…”
Section: Anti-nutrition Of Protein Concentrate Of Cp-jsc Post Fermentmentioning
confidence: 97%
“…Most protease inhibitors or anti trypsin are proteins with domains that enter or block a protease active site to prevent substrate access. According to protein content, there is no difference among treatments but Akande and Balogun (2009) reported that protein and trypsin inhibitor contents were negatively correlated.…”
Section: Anti-nutrition Of Protein Concentrate Of Cp-jsc Post Fermentmentioning
confidence: 97%